Mouse brain transcriptome responses to inhaled nanoparticulate matter differed by sex and APOE in Nrf2-Nfkb interactions - Amin Haghani; Mafalda Cacciottolo; Kevin R Doty; Carla D'Agostino; Max Thorwald; Nikoo Safi; Morgan E Levine; Constantinos Sioutas; Terrence C Town; Henry Jay Forman; Hongqiao Zhang; Todd E Morgan; et al. (eLife, 2020)
The neurotoxicity of air pollution is undefined for sex and APOE alleles. These major risk factors of Alzheimer’s disease (AD) were examined in mice given chronic exposure to nPM, a nano-sized subfraction of urban air pollution. In the cerebral cortex, female mice had two-fold more genes responding to nPM than males. Transcriptomic responses to nPM had sex-APOE interactions in AD-relevant pathways. Only APOE3 mice responded to nPM in genes related to Abeta deposition and clearance (Vav2, Vav3, S1009a). Other responding genes included axonal guidance, inflammation (AMPK, NFKB, APK/JNK signaling), and antioxidant signaling (NRF2, HIF1A). Genes downstream of NFKB and NRF2 responded in opposite directions to nPM. Nrf2 knockdown in microglia augmented NFKB responses to nPM, suggesting a critical role of NRF2 in air pollution neurotoxicity. These findings give a rationale for epidemiologic studies of air pollution to consider sex interactions with APOE alleles and other AD-risk genes.